ERRATUM (The Accounting Review, 2024)
The publisher, American Accounting Association, regrets an error in “Understanding the Sustainability Reporting Landscape and Research Opportunities in Accounting” by Patricia M. Dechow in the September 2023 issue (Volume 98, Number 5, pp. 481–493; https://doi.org/10.2308/TAR-2023-0145) of The Accounting Review. Milton Friedman’s name was misspelled in the sentence prior to his quote.The online version of the article has been corrected (as shown below). The error only exists in the printed version.